Rare Site of an Inflammatory Myofibroblastic Tumor at the Epididymis: A Case Report - Lange A; Dominiak N; Petros FG (Cancer Management and Research)
Alyssa Lange,1 Nicole Dominiak,2 Firas G Petros1 1Department of Urology, College of Medicine and Life Sciences, The University of Toledo, Toledo, OH, USA; 2Department of Pathology, College of Medicine and Life Sciences, The University of Toledo, Toledo, OH, USACorrespondence: Firas G Petros, Department of Urology, The University of Toledo College of Medicine and Life Sciences, 3000 Arlington Ave. Mail Stop 1091, Toledo, Ohio, 43614-2598, USA, Tel +1(419).383.3584, Fax +1(419).383.3785, Email firas.petros@utoledo.eduBackground: Inflammatory myofibroblastic tumors (IMT) are uncommon with an estimated 150– 200 people being diagnosed in the US annually. We describe a healthy adult male who presented with an enlarging, painless scrotal mass. Based on current literature, only nine epididymal inflammatory myofibroblastic tumors have been reported and in this case report we describe the tenth.Case Presentation: A 40-year-old Caucasian male presented with an enlarging mass near his right testicle with no associative symptoms or obvious etiology. Scrotal ultrasound showed a solid heterogenous mass with internal vascularity. Tumor markers were unremarkable for lactate dehydrogenase (LDH), beta-human chorionic gonadotropin (b-hCG), and alpha-fetoprotein (AFP). A right inguinal approach was performed. A 2– 3 cm round mass adjacent to the tail of the epididymis was excised with clear margins and sent to pathology. Histology confirmed a 2.4 cm inflammatory myofibroblastic tumors with scattered positivity for smooth muscle actin, negative pancytokeratin, and negative anaplastic lymphoma kinase. Patient recovered well with no reoccurrence at this time.Conclusion: Inflammatory myofibroblastic tumors recurrence rate is < 2%; however, some literature suggests higher depending on location and immunohistochemical profile. The expertise of pathologists, utilization of morphology, and immunohistological profile are all crucial in accurate diagnoses of these lesions. Literature reports some lesions have demonstrated metastatic tendencies and therefore complete excision of the mass is the recommended therapy of choice. This case highlights the increasing need to include IMT in differential diagnoses for patients presenting with painless lumps even in unlikely locations. While there is little data on epididymal tail mass recurrence rate potential, we report no current recurrence after complete excision of the mass.Keywords: paratesticular tumor, IMT, epididymis, intrascrotal mass